2021
DOI: 10.1021/acsami.1c01155
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Potassium Storage Performance for K-Te Batteries via Electrode Design and Electrolyte Salt Chemistry

Abstract: Potassium batteries are an emerging energy storage technology due to the large abundance of potassium, low cost, and potentially high energy density. However, it remains challenging to find suitable electrode materials with high energy density and good cycling stability due to the structural instability and kinetics issues resulting from large size K+. Herein, a durable and high-capacity K-Te battery was developed by rational design of a Te/C electrode and electrolyte salt chemistry. A well-confined Te/C catho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 61 publications
1
20
0
Order By: Relevance
“…The large specific capacity difference between 1st and 2nd might be due to the formation of solid electrolyte interphase. [15] Regardless, Figure S8 (Supporting Information) validates the applicability of our CGPE in K-Te battery system.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…The large specific capacity difference between 1st and 2nd might be due to the formation of solid electrolyte interphase. [15] Regardless, Figure S8 (Supporting Information) validates the applicability of our CGPE in K-Te battery system.…”
Section: Resultssupporting
confidence: 64%
“…C 1s spectra could be decomposed into three peaks at 289.5, 285.0, and 283.6 eV, attributed to OCO, COC, and CC, respectively. [15] The existence of CO and CO bonds is confirmed by the peaks at 532.0 and 531.1 eV in O 1s spectra (Figure 3e). The intense peak at 686.7 eV and the weak peak at 682.0 eV are assigned to SF and KF bonds, respectively, originating from the KFSI salt.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Moreover, the pore structure is critical in affecting K‐ion storage capacity and reaction pathways for K‐Te batteries. Our group reported a Te/C cathode with activated carbon (ASAC25) as the Te host and this Te/ASAC25 cathode possessed only one pair of anodic/cathodic peaks in the same voltage range of 0.5–3 V, [ 36 ] suggesting a one‐step electrochemical conversion from Te to K 2 Te or K 5 Te 3 . This Te/ASAC25 showed stable cycling performance without significant capacity fading after 100 cycles at 0.2 C because of the effective Te confinement by highly microporous carbon.…”
Section: Resultsmentioning
confidence: 99%
“…The excellent cycling stability was achieved with a specific capacity of 215.5 mAh g −1 after 100 cycles at 5C due to the superb immobilization of Te nanoparticles on the G‐CNT matrix. On the other hand, Liu et al [ 36 ] reported an enhanced K‐Te battery via rational design and electrolyte chemistry. Potassium hexafluorophosphate (KPF 6 ) was found to facilitate electron transfer and K‐ion diffusion, thus boosting redox kinetics and K‐ion storage performance.…”
Section: Introductionmentioning
confidence: 99%